Songs of Seoul : an ethnography of voice and voicing in Christian South Korea - Harkness, Nicholas (University of California Press, 2014)
Songs of Seoul is an ethnographic study of voice in South Korea, where the performance of Western opera, art songs, and choral music is an overwhelmingly Evangelical Christian enterprise. Drawing on fieldwork in churches, concert halls, and schools of music, Harkness argues that the European-style classical voice has become a specifically Christian emblem of South Korean prosperity. By cultivating certain qualities of voice and suppressing others, Korean Christians strive to personally embody the social transformations promised by their religion: from superstition to enlightenment; from.